Anemia pada Ibu Bersalin dengan Berat Badan Lahir Bayi - Ni Nyoman Hartati; Ni Luh Nilam Shanti Cahyani; I Dewa Made Ruspawan (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2020)
The maternal mortality rate in Indonesia is still very high. One of the factors causing high MMR in Indonesia is a pregnancy disorder, one of which is anemia. This study aims to determine the relationship of anemia in maternity with birth weight in Wangaya Hospital in 2019. The type of research is correlational analytic with a crosssectional approach. The sample was anemic mothers who gave birth in Wangaya Hospital in 2019 using purposive sampling and obtained 108 samples analyzed using the Spearman Rank test with (value) p = 0,000 (p value ≤ 0.05 and correlation coefficient (r ) = 0.742. The results can be concluded there is an association of anemia in maternity with birth weight, the lower the mother's Hb, the lower of the baby born.